Analisis Kepuasan dan Loyalitas Petani Terhadap Penggunaan Benih Jagung Hibrida di Desa Bangkok Kecamatan Gurah Kabupaten Kediri (Agridevina : Berkala Ilmiah Agribisnis, 2022)
This research aimed to analyze farmer satisfaction level and loyality level to Corn Hybrid seed in the village of Bangkok, Gurah subdistrict, Kediri regency. Population in this research is farmers who used the P-21 Hybrid Corn seed at least 3 times and had rice fields for corn cultivation. Sampling method of Slovin formula and the number of samples considered representative and reflects the characteristic of the population is 50 respondents with the help of questionnaires. The results of the analysis based on the level of satisfaction of attributes based on IPA are 4 attributes of the I or top priorities, namely productivity, pest and disease resistance, seed price, and product price. The level of satisfaction of a CSI based attribute of 76.91% or on a range scale indicates "satisfied". The farmer's loyalty test that using the P-21 corn seed is still low has not formed an inverted triangle, or belongs to the category "switcher buyer". DOI : https://doi.org/10.33005/agridevina.v11i2.3530